Kewenangan dan Pengawasan Pemerintah dalam Regulasi Pembentukan Koperasi Desa Merah Putih - Simorangkir, Debora Juliani; Sinaga, Parbuntian; Setyowati, Retno Kus (Pusat Riset dan Inovasi Nasional, 2025)
In the Indonesian economic system, cooperatives play a crucial role as one of the pillars of the national economy, as mandated in Article 33 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. This article emphasizes that